Individual performance after success and failure: A natural experiment - Christoph Bühren; Stefan Krabel (Philipps-University Marburg, Faculty of Business Administration and Economics, 2015)
The main goal of our study is to analyze how success and failure in crucial situations affect subsequent individual performance. Our study is based on evidence from a natural experiment of NBA (National Basketball Association) players: Based on play-by-play statistics of NBA games in 10 seasons (1818 observations of 345 sportsmen), we identify players who are responsible for the overtime by taking the last shot of the game. Players who miss the shot when the game is tied perform better in overtime than in the last quarter (within-subject comparison) but not significantly different to their game and season averages. Players who score the equalizer in the last shot of the regular game perform substantially worse in overtime compared to their 4th quarter performance as well as compared to their game and season averages. Yet the average performances in overtime of both groups do not differ significantly (between-subject comparison). We conclude that success in crucial situations leads to lower subsequent individual performance. Psychological explanations for this phenomenon, e.g. the role of overconfidence, are discussed. We argue that our findings can be transferred to behavior after success or failure in business settings since we have distinct identifications of performance and responsibility: the observed overtimes are clear and immediate outcomes of the last shots of our analyzed players; without their success or failure, the game would have been over after regular time.
Keywords: C93; 330; success; failure; performance; psychological pressure; overconfidence; hot hand fallacy; natural experiment; basketball; NBA